Effectiveness of the “Lari Tangkap Zona” Game as a Warm-Up Method to Improve Students’ Physical Fitness - Frekdi Alosius Manik; Ade Ros Riza; Daphne Rudi Sialahi; Falih Ariq Subakti; Rudy Kharunia Harahap; Syalwa Octavia; Faridz Hilmy Karo Karo; Jiyad Hawari; Badriatha Wafianto; Ika Oktarina br Kaban (INSPIRETECH GLOBAL INSIGHT & (ISORI KAMPAR), 2026)
Purpose of the Study: This study aims to analyze the effectiveness of the lari tangkap zona game as a warm-up method to improve students’ physical fitness. The game was examined as an alternative warm-up activity that is engaging, developmentally appropriate, and aligned with the characteristics of learners in Physical Education setting. Materials and Methods: A quantitative research approach was employed using a pre-experimental one-group pretest–posttest design. The research subjects consisted of students participating in Physical Education learning at school. Physical fitness was assessed using a fitness test covering endurance, speed, agility, and strength components. Pretest and posttest measurements were compared to determine changes in fitness outcomes. Results: The findings reveal a significant improvement in students’ physical fitness after participating in warm-up activities using the lari tangkap zona game. Positive changes were observed across nearly all fitness indicators, as reflected by higher posttest scores compared to pretest results. The game not only enhanced physical fitness but also increased students’ motivation and active participation during the learning process. Conclusions: The lari tangkap zona game is an effective and enjoyable warm-up method that supports improvements in students’ physical fitness. Its playful format encourages engagement and promotes comprehensive fitness development. Therefore, this game is recommended for use in Physical Education warm-up sessions to optimize students’ readiness and physical conditioning.